Differing impact of preterm birth on the right and left atria in adulthood - Schuermans, A; den Harink, T; Raman, B; Smillie, RW; Alsharqi, M; Mohamed, A; Lapidaire, W; van Deutekom, AW; Leeson, P; Lewandowski, AJ (American Heart Association, 2022)
Background Preterm birth affects 10% of live births and is associated with an altered left ventricular and right ventricular phenotype and increased cardiovascular disease risk in young adulthood. Because left atrial (LA) and right atrial (RA) volume and function are known independent predictors of cardiovascular outcomes, we investigated whether these were altered in preterm‐born young adults.